Evaluasi Tingkat Kapabilitas Tata Kelola Teknologi Informasi dengan Kerangka Kerja COBIT 5 pada Proses APO01 dan APO07 di Dinas Komunikasi dan Informatika Provinsi Jawa Timur - Nanda Fiesta Farada; Andi Reza Perdanakusuma; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Komunikasi dan Informatika (KOMINFO) Provinsi Jawa Timur is an organization or government agency that has a role in managing informatics and realizing a smart province program. Based on the document Perubahan Renstra KOMINFO in the 2014-2019, it is stated that in realizing smart province there are 3 success factors. Those are technological, human and institutional factors. However, in practice KOMINFO has not yet conducted an evaluation related to this matter, where it should be one of the agendas carried out periodically to ensure whether the performance that has been carried out is appropriate or meets the government regulations that have been set. In this research, COBIT 5 was used to evaluate the capability level in the APO01 (Manage the IT Management Framework) and APO07 (Manage Human Resources). The first stage is mapping the RACI Chart to determine the Responsible respondents, then collecting data by doing observation, interviews, and document studies to determine the capability level of each process, then conduct data validation, gap analysis, and recommendations for improvements in the form of roadmap. The APO01 process is at level 3 of 78% with a gap of 1 level and the APO07 process is at level 1 at 81% with a gap of 2 levels. There are 8 recommendations for the APO01 process and 11 recommendations for the APO01 process, one of the recomendation is to make a quality record of the application of the established SOPs.